Identification of mobile devices by the characteristics of the spectra and their signals - Антипов, И.Е.; Василенко, Т.А. (Radiotekhnika, 2020)
Previously, the authors suggested that each range of Wi-Fi devices is as unique as a fingerprint. This paper presents the results of an experimental verification of the assumption. Several devices were tested in different positions relative to the measuring antenna of the Signal Hound USB-SA44B spectrum analyzer. The similarity of the spectra of Wi-Fi signals of the same device in different positions and the significant differences in the emission spectra of different devices, which can be used to identify them, are established. The range of mean squares of the differences in the spectral counts is established, which can correspond to the same device in different positions and to different devices. The difference value is less than 1.5 dB, then this is definitely the same device. If the difference is greater than 2.8 dB, then it is obvious that these are different devices. The range of 1.5 ... 2.8 dB represents an area of uncertainty – such differences can relate to the same device or to different ones. The effect of temperature was also investigated. Spectra of the same smartphone at room temperature and at a temperature of +5 0C without correction for frequency shift. Then, to take into account the frequency shift, a correction was made that allowed “shifting” the spectrum of the cooled device to its original state. Lowering the temperature leads not only to a shift in the average frequency of the spectrum, but also to a change in its shape. The results of experimental studies on measuring the spectrum of mobile devices indicate the applicability of this method for identifying mobile devices, which will qualitatively complement the existing security model, reducing the risks of unauthorized actions.